Online Gaming Addiction and Quality of Life among Early Adolescents in Thailand: An Investigation from a SEM-Neural Network Approach - Veera Bhatiasevi; Pungpond Rukumnuaykit; Piriya Pholphirul (Human Behavior and Emerging Technologies)
The popularity of gaming has greatly increased, especially among children and adolescents. As such, spending too much time playing games has become a serious issue and may have adverse effects on the quality of life of adolescents. This paper is aimed at identifying the factors and degree of influence that leads to gaming addiction and its impact on the quality of life of Thai adolescents. Data were collected from 2,044 adolescents in the form of a questionnaire from five major regions in Thailand, in both municipal and nonmunicipal areas. Structural equation modeling and the neural network model were used to analyze the data. The results indicate some differences between boys and girls as to what factors lead to gaming addiction. But gaming addiction was found to have a negative impact on the quality of life for both genders. Discussions comprising both academic and practical perspectives are also presented.